Navigating the image discrepancy: A grounded theory approach to understanding Malaysia’s image among Chinese tourists - Xiaocong Jiang; Ahmad Edwin bin Mohamed; Amirul Husni bin Affifudin (PLoS ONE, 2025)
The number of Chinese tourists visiting Malaysia has not returned to pre-pandemic levels, raising concerns that recent negative news stories widely circulated on Chinese social media may be a contributing factor. Due to the limited number of reviews, sentiment analysis struggles to determine whether negative news significantly affects tourists’ emotions and visitor numbers. This study employs empirical data to validate its impact, clarifying its actual influence on image discrepancy and tourist arrivals. Additionally, while managing image discrepancy is acknowledged as important in tourism, academic debate persists regarding whether negative news contributes to these discrepancies. This study conducted in-depth interviews with 30 participants, comprising 18 individual attendees and 12 attendees from 4 small seminars. Participants included recent visitors to Malaysia, prospective tourists who canceled their plans, and Malaysian tourism practitioners. Using the Context-Adaptive Grounded Theory (CAGT) methodology, the study explored whether sudden negative news events significantly influence Chinese tourists’ travel decisions and identified specific factors contributing to the discrepancy between Chinese tourists’ perceptions of Malaysia’s tourism image and the image projected by Destination Marketing Organizations (DMOs). The findings revealed that negative news was not the dominant factor driving image discrepancy. Instead, cultural differences—stemming from unclear understanding of religious and local cultures, as well as language barriers—were the primary causes. Additionally, inefficiencies in DMOs’ promotion of Malaysia’s multi-ethnic identity and an overemphasis on medical tourism, which failed to attract Chinese tourists, were identified as secondary factors. This study provides valuable insights into the complex impact of sudden events on tourism and offers guidance for Destination Management Organizations to better align projected and perceived destination images to facilitate tourism recovery.